Potential for Drought Tolerance in Cowpea - Magie Mereena (Department of Plant Breeding, College of Agriculture, 1989)
A research programme was carried out at the department of plant breeding, College of Agriculture, Vellayani, Trivandrum during 1988 with sixteen varieties of cowpea for studying the potential for drought tolerance. The date on twentysix characters and soil moisture percentage in different plots were collected and subjected to analysis of variance/covariance. The genetic variability and correlations were estimated for the characters contributing to drought tolerance, yield and its components. The path analysis was conducted using yield as the effect and seven components contributing to drought tolerance as causes. Analysis of variance for twentysix characters revealed that significant differences existed among varieties for all the characters except for root spread at vegetative period. The analysis of variance for soil moisture percentage showed no significant difference among experimental plots indicating uniform soil moisture status in all the plots. High genotypic coefficient of variation, moderate to high heritability and high genetic advance was shown by characters such as leaf area index at vegetative, flowering and harvest periods, number of pods per plant, hundred grain weight, and proline content. Harvest index also had moderately high heritability and genetic advance. This indicates the reliability of the above components during selection programmes for the improvement of yield. Grain yield per plot showed positive genotypic correlation with leaf area index at vegetative and flowering period, root spread at harvest period, number of pods per plant, root/shoot ratio at vegetative period, grain filling period, and plant height at maturity. Path analysis revealed that harvest index and leaf area index at vegetative period had maximum positive direct effect on yield. Based on the studies on variability, correlation and path analysis it can be concluded that a plant type. Suited to drought conditions should be early flowering with deep and wide spread root system, high root/shoot ratio and leaf area index at vegetative period, low proline content, few number of stomata, long grain filling period and medium duration resulting in the production of more number of pods per plant and high harvest index. The cowpea varieties UPC-124, DPLC-198 and DPLC-216, satisfying the above plant type can be considered as drought tolerant.